Morphological and mechanical characterization of chitosan/gelatin/silica-gentamicin/bioactive glass coatings on orthopaedic metallic implant materials - Aydemir, Tuba; Pastore, Juan I.; Jimenez-Pique, Emilio; Roa, Joan Josep; Boccaccini, Aldo R.; Ballarre, Josefina (Thin Solid Films, 2021)
Metals are the most widely used materials for orthopedics and dentistry due to their high mechanical properties. However, for certain uses like fixation plates and screws, dental implants, and osseo-articular prosthesis, their surface characteristics such as non-toxic and non-corrosive behavior, good cell adhesion and proliferation, and resistance to bacterial biofilm formation should be accompanied with high mechanical performance. One way to improve metallic implant performance in vivo is to coat them with biopolymer or inorganic thin films. This work describes two multifunctional coating systems for orthopedic titanium and stainless steel implants. Titanium implants were coated with a system consisting of a base hybrid sol-gel layer with bioactive glass particles (applied via spraying) and a top chitosan/gelatin layer with silica-gentamicin nanoparticles (applied via electrophoretic deposition, EPD). Stainless steel implants, which are designed to be removable, were coated only with the top chitosan/gelatin/ silica-gentamicin nanoparticles layer with the aim of providing a temporal attachment to bone and to combat possible bacterial adhesion. The microstructural and mechanical characterization of the coatings was conducted by optical microscopy, transmission and scanning electron microscopy, digital image processing, as well as nanoindentation and nanoscratch tests to advance the understanding of their elastic-plastic, morphologic and adhesive behavior. The coatings were homogeneous, providing good coverage to both substrates. Their surface properties, such as roughness and wettability, indicate that they represent excellent substrates for cell attachment. Bioactive glass particles can be added to titanium implant systems as bioactive components without affecting adhesion or mechanical performance of the chitosan/gelatin/silica-gentamicin nanoparticle EPD coatings. The increase in both hardness and elastic modulus of the coated systems could be due to the presence of the silica-gentamicin nanoparticles and their compaction during the penetration of the indenter. When the samples are subjected to scratch tests, the critical load increases with the reinforcement of the coatings by the silica-gentamicin nanoparticles absorbing the applied load and maintaining the elastic properties of the coatings.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Bioactive glasses; Biopolymers; Electrophoretic deposition; Functional coatings; Mechanical properties; Metallic implants